Evaluation of packaging materials for enhancing the storage life of marigold flowers (Tagetes erecta) - KUMAR, MYADAM NAVEEN; JAIN, RITU; SINGH, M C; TIWARI, A K; SINGH, BABITA; SETHI, SHRUTI; SATHEE, LEKSHMY; LAL, KHAJANCHI; KUMAR, AMRENDER; MADHAVI, K (The Indian Journal of Agricultural Sciences, 2024)
Among the various loose flower crops, marigold (Tagetes erecta L.) holds a prominent place among commercial crops. Its vibrant blooms are in high demand, but flowers are perishable, rendering them susceptible to significant post-harvest losses. Efforts to mitigate these losses will enhance the overall flower production, distribution to maximize its economic potential and to sustain valuable contribution for the industry. So, the present experiment on storage of marigold flowers was conducted during 2021 and 2022 at the ICAR- Indian Agricultural Research Institute, New Delhi with an objective to improve the shelf life of flowers by using different packaging materials. The results revealed that in marigold var. Pusa Basanti Gainda, maximum shelf life, high carotenoid content, minimum ion leakage, physiological loss in weight and enzyme activity were achieved in flowers packed in shrink-wrap and stored under low-temperature (6±20C) conditions.